Influência de uma árvore isolada de freixo (Fraxinus angustifolia Vahl ) no microclima num lameiro em Trás-os-Montes - Abreu, Francisco Gonçalves (2009)
Changes in microclimate caused by an isolated ash tree (Fraxinus angustifolia Vahl) were assessed in a pasture land close to Bragança (41º 46’ 55’’ N; 6º 24’ 51’’ W; 510m de altitude), in Northeastern Portugal), where climate is Csb according to Köppen. The experimental site was locatedin the bottom of a small valley, and soils mostly fit the Eutric Fluvisols. Solar radiation, rainfall, and air and soil temperature were measured during three years beneath the tree canopy and in the open. Results showed that the microclimate conditions under the tree canopy were significantly different from those in the open. This is due to solar radiation interception (about 25 a 35% in winter and 55 a 65% in summer) and the interception of about 40% of the gross rainfall (52-56% during May- -October, and 35% when the foliage was absent). Mean air temperatures under the canopy were higher than those in the open, with the differences being greater at nigth, reaching about 3ºC in summer and 5ºC in winter. Compared to the open, mean soil temperatures in winter were higher (about 1ºC at 20 cm depth) beneath the canopy, but were smaller (1ºC at 2 cm depth) in summer. Amplitudes of soil and air temperature were lower under the tree canopy than in the open. These microclimate conditions under the canopy may favour both the herbaceous biomass production and the earlier development of herbaceous at the end of winter.